Blockade of Rennin-Angiotensin system blunts the fibrotic response in experimental acute pyelonephritis - Singal A; Bajpai M; Dinda A (Wolters Kluwer Medknow Publications, 2005)
Aim: To study the impact of Renin-Angiotensin system blockade in experimental acute pyelonephritis, induced by a novel surgical approach via dorsal lumbotomy incision. Materials and Methods : 45 Adult female WISTAR rats aged 8-12 weeks, underwent direct inoculation of 0.1 ml of E.coli suspension into the parenchyma of the surgically exposed kidney. 3 groups of rats were studied: Group A - treated with antibiotics only; Group B- Captopril and antibiotics and Group C- Losartan and antibiotics. Changes of acute inflammation, parenchymal destruction and scarring were compared between the groups on histopathological sections. Kruskal-Wallis test was used for statistical analysis. Results : Changes consistent with acute pyelonephritis were seen in all the kidneys. Mean% scar area in Group A, Group B and Group C was 37.08±1.79, 24.40±1.88 and 24.68±1.32% respectively at end of six weeks. Mean tubular density in Group A, B and C was 17.26±1.92, 47.18±3.00 and 47.00±5.08-tubules/lac mm2 respectively. The differences between the control and the treated animals were significant, though the results did not differ between the losartan and captopril treated rats. Conclusions : Dorsal lumbotomy approach to the kidney provides a good exposure of the kidney. Induction of acute pyelonephritis by direct inoculation of bacteria into renal cortex produced a consistent scar at 6 weeks. Blockade of renin angiotensin system by either captopril or losartan decreased the renal scar area by almost 1/3 at 6 weeks.